2022
DOI: 10.1021/acs.iecr.2c01123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound and Its Amplitude on the Metastable Zone Width, Induction Time, and Nucleation Kinetics of Pyrazinamide in Acetone

Abstract: A systematic investigation is carried out to analyze the effect of ultrasonic amplitudes (10, 30, and 50%) on the metastable zone width (MSZW) and induction time (t ind ) for unseeded batch cooling crystallization of pyrazinamide from its acetone solution. The MSZW is measured at five different saturation temperatures (293.15, 298.15, 303.15, 308.15, and 313.15 K) with different cooling rates. Five cooling rates (30, 24, 18, 12, and 6 K/h) were selected for the silent case, and three cooling rates (24, 18, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…The interfacial energy was calculated via the induction time data based on CNT, and then compared with the results of PTM to verify the dependability of the experimental data. The extrapolated MSZW of Pyrazinamide in acetone from induction time data via concept of nucleation potential was reliable for lower saturation temperatures . Even in an electrolyte system, the estimated MSZWs also showed improved accuracies and a tendency to be positively correlated with both the supersaturation temperature and cooling rate .…”
Section: Introductionmentioning
confidence: 90%
“…The interfacial energy was calculated via the induction time data based on CNT, and then compared with the results of PTM to verify the dependability of the experimental data. The extrapolated MSZW of Pyrazinamide in acetone from induction time data via concept of nucleation potential was reliable for lower saturation temperatures . Even in an electrolyte system, the estimated MSZWs also showed improved accuracies and a tendency to be positively correlated with both the supersaturation temperature and cooling rate .…”
Section: Introductionmentioning
confidence: 90%
“…The induction period ( t ind ), a crucial kinetic parameter, was employed to investigate the selective interactions between chiral solvents and solutes . The determination of t ind of Thr enantiomeric crystals in water and CCM-0.3 was performed by a laser method at 283.15 K, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The induction period (t ind ), a crucial kinetic parameter, was employed to investigate the selective interactions between chiral solvents and solutes. 34 The determination of t ind of Thr enantiomeric crystals in water and CCM-0.3 was performed by a laser method at 283.15 K, respectively. First, saturated solutions of Thr enantiomers in water and CCM-0.3 were prepared at seven temperatures higher than 283.15 K, respectively.…”
Section: = M Mmentioning
confidence: 99%
“…18 Maharana and Sarkar investigated the effect of ultrasound on the metastable zone width of pyrazinamide from acetone solution and found that application of ultrasound increased the nucleation rate constant by 2-to 3-fold. 21 Zhao et al measured the metastable zone width of nicotinic acid in ethanol and revealed that temperature and driving force jointly affect the metastable zone width and nucleation rate. 28 Cao et al studied the nucleation behavior of isosorbide 5-mononitrate by metastable zone width, during which the Nyvlt's equation and modified Sangwal's theory were employed to obtain nucleation kinetic parameters.…”
Section: Introductionmentioning
confidence: 99%